2022
DOI: 10.3390/medicina58111539
|View full text |Cite
|
Sign up to set email alerts
|

The Oncological Implication of Sentinel Lymph Node in Early Cervical Cancer: A Meta-Analysis of Oncological Outcomes and Type of Recurrences

Abstract: Background and Objectives: Pelvic lymphadenectomy has been associated with radical hysterectomy for the treatment of early Cervical Cancer (ECC) since 1905. However, some complications are related to this technique, such as lymphedema and nerve damage. In addition, its clinical role is controversial. For this reason, the sentinel lymph node (SLN) has found increasing use in clinical practice over time. Oncologic safety, however, is debated, and there is no clear evidence in the literature regarding this. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similarly, in patients with ECC ≥ 2 cm, the modalities of lymphadenectomy are also controversial. Despite the high risk of lymph node metastasis, using the sentinel lymph node (SLN) could minimize the risks of lymphadenectomy-related morbidity 37 , 38 and provide information on the presence or absence of micrometastases by ultrastaging. 39 The upstream intent would be to identify patients with positive lymph nodes to exclude them from the FST pathway, regardless of the ART or NACT approach.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in patients with ECC ≥ 2 cm, the modalities of lymphadenectomy are also controversial. Despite the high risk of lymph node metastasis, using the sentinel lymph node (SLN) could minimize the risks of lymphadenectomy-related morbidity 37 , 38 and provide information on the presence or absence of micrometastases by ultrastaging. 39 The upstream intent would be to identify patients with positive lymph nodes to exclude them from the FST pathway, regardless of the ART or NACT approach.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, SLNB, when adhering to the algorithm, offers higher negative predictive value (NPV), specificity, and sensitivity compared to imaging staging. Regarding the survival outcomes of SLNB vs. PLNB, no clear inferiority of the former was demonstrated by a systematic review and meta-analysis [ 21 ], while one systematic review [ 13 ] was retrieved that showed the high diagnostic accuracy in terms of NPV and sensitivity. Additionally, regarding the impact of low-volume disease, two retrospective cohort studies showed conflicting results, with micrometastases (MICs) being associated with increased and decreased survival rates [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta-analysis was conducted to address this question, including four studies, of which one was prospective randomized multicentric study, while the remaining three were retrospective cohorts [ 21 ]. The meta-analysis encompassed 1952 patients of FIGO Stage IA1 to IIA, with 383 undergoing exclusively SLNB and 1569 undergoing PLND.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis was conducted to address this question including 4 studies, of which one was prospective randomized multicentric study, while the remaining three were retrospective cohorts [21]. The meta-analysis encompassed 1,952 patients of FIGO Stage IA1 to IIA, with 383 undergoing exclusively SLNB and 1,569 undergoing PLND.…”
Section: Sentinel Node Vs Systematic Lymphadenectomymentioning
confidence: 99%